ЕЛЕКТРОМАГНІТНІ ПРОЦЕСИ В ЛИСТОВИХ НЕМАГНІТНИХ МЕТАЛАХ ПІД ЧАС МАГНІТО-ІМПУЛЬСНОЇ ОБРОБКИ ШВІВ В ПРОЦЕСІ ЗВАРЮВАННЯ - Кондратенко, І.П.; Крищук, Р.С.; Лобанов, Л.М.; Пащин, М.О.; Миходуй, О.Л.; Тимошенко, О.М. (Інститут електродинаміки НАН України, Київ, 2026)
Residual tensile stresses in welded joints negatively affect the fatigue strength, corrosion resistance, and dimensional accuracy of metal structures. Treatment with a pulsed electromagnetic field allows for optimization of the stress state and metal microstructure of the welded joints, thereby contributing to enhanced reliability and longevity of structures, and consequently extending their operational lifespan. The aim of this work is to determine, through mathematical modeling, the distribution of the electromagnetic field and magnetic forces within the volume of a weld seam in an aluminum alloy plate with isotropic parameters during its treatment by the magnetic field of an inductor with pulsed current. A three-dimensional mathematical model of the induction system was developed to calculate the electromagnetic field equations. The calculation of pulsed current in the inductor winding conductors along with the electromagnetic field of the entire induction system was performed using electrical circuit equations based on Kirchhoff's second law and electromagnetic field equations based on Maxwell's equation system. A comparison of magnetic forces, field strength, and eddy current density in the weld seam area was conducted for plates with thicknesses of 6 mm and 3 mm. The 6 mm plate can be interpreted as two 3 mm plates, one with a weld seam and the other acting as a screen, which allowed investigation of such screening effect on force and current distribution. A study was conducted of the vector quantities of field strength, current density, and magnetic forces in the volume of the weld seam area being treated, as a function of time. Based on the developed methodology, experimental studies were performed to assess the impact of magneto-pulse treatment on residual welding stresses and the metal microstructure of welded joints made of AMg6 aluminum alloy. It was demonstrated that treating the weld metal during or after welding contributes to reducing residual tensile stresses and dispersing the microstructure of the weld metal. References 16, figures 11, tables 2.